Demystifying Switched Capacitor Circuits - Liu, Mingliang (Michael)
This book helps engineers to grasp fundamental theories and design principles by presenting physical and intuitive explanations of switched-capacitor circuits. Numerous circuit examples are discussed and the author emphasizes the most important and fundamental principles involved in implementing state-of-the-art switched-capacitor circuits for analog signal processing and power management applications. Throughout the book, the author presents numerous step-by-step tutorials and gives practical design examples. While some quantitative analysis is necessary to understand underlying concepts, tedi.